Woods to goods: Water consumption analysis for papermaking industry in China. (10th September 2018) - Man, Yi; Han, Yulin; Wang, Yifan; Li, Jigeng; Chen, Ling; Qian, Yu; Hong, Mengna
Abstract: Papermaking is a water intensive industry. The growth of paper demand will further intensify the need of fresh water resources. Papermaking involves complex processing routes. Previous investigations of water consumption in papermaking industry have focused primarily on key processes and pathways, ignoring the impacts of many intermediate and inter-related processes in paper production cycles and there underestimating the sustainability impacts. Herein, the results of a life cycle analysis of water consumption for papermaking industry in China using an extensive system boundary that includes the water embedded in intermediate processing are presented. The results show the life cycle water consumption and water saving potentials for different papermaking pathways. The advocacy of "forest pulp and paper integration" may have few practical contribution to reducing water consumption due to the low indirect water consumption of raw materials and energy for transportation. Highlights: Life cycle water consumption for papermaking industry in China is quantitatively analyzed. Direct water consumption and indirect water consumption from energy supply are analyzed. Life cycle pathways for all kinds of pulp and paper productions are involved.